2022
DOI: 10.4317/jced.59129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of Er:YAG laser, and EDTA, MTAD, and QMix irrigants on adhesion of stem cells from the apical papilla to dentin: A scanning electron microscopic study

Abstract: Background Dentin conditioning can affect the adhesion of stem cells in endodontic regenerative treatments. This study aimed to assess the effects of the most commonly used endodontic irrigants, namely, ethylenediaminetetraacetic acid (EDTA), MTAD, and QMix in comparison with Er:YAG laser (as a novel modality for root canal disinfection) on the adhesion of stem cells from the apical papilla (SCAPs) to dentin. Material and Methods Forty dentin specimens were prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Although its pH is slightly alkaline, we used it in our study because it has the antimicrobial properties of chlorhexidine along with the smear-layer removal properties of EDTA. 21,22 Importantly for our study, Al-Sheik Abidal et al 23 showed that QMix had bactericidal properties toward E. faecalis. Furthermore, Kalyoncuoglu et al 24 found that QMix was shown to be effective against C. albicans when used as final irrigation.…”
Section: Discussionmentioning
confidence: 58%
“…Although its pH is slightly alkaline, we used it in our study because it has the antimicrobial properties of chlorhexidine along with the smear-layer removal properties of EDTA. 21,22 Importantly for our study, Al-Sheik Abidal et al 23 showed that QMix had bactericidal properties toward E. faecalis. Furthermore, Kalyoncuoglu et al 24 found that QMix was shown to be effective against C. albicans when used as final irrigation.…”
Section: Discussionmentioning
confidence: 58%
“…An in vitro study by Rahmati et al 36 evaluated the effect of dentin conditioning by different endodontic irrigants (EDTA, MTAD, and QMix), compared to the Er:YAG laser, on the adherence of stem cells to dentin. Forty dentin specimens were prepared and divided into five groups: control, irrigation with EDTA, irrigation with MTAD, irrigation with QMix, and Er:YAG laser irrigation.…”
Section: Laser-activated Irrigationmentioning
confidence: 99%
“…Additionally, due to its inadequacy in removing the smear layer alone, it is necessary to use two or more irrigation solutions sequentially. Therefore, combined irrigation solutions such as QMix (Dentsply Tulsa, Maillefer, Ballaigues, Switzerland) and MTAD (Dentsply, Tulsa Dental, Tulsa, OK, USA) have also been introduced to the market after irrigation with NaOCl [ 11 ].…”
Section: Introductionmentioning
confidence: 99%